Efficacy of Percutaneous Nephrolithotomy in Pediatric Renal Stone Clearance in Khyber Pakhtunkhwa: A Cross-Sectional Analytical Study: Percutaneous Nephrolithotomy in Pediatric Renal Stone Clearance - Khan, Waqas; Khan, Tariq Saleem; Khan, Riaz Ahmad; Khalid, Muhammad; Ahmad, Abrar; Khan, Asad Iqbal (Pakistan Journal of Health Sciences, 2025)
Renal stone disease is increasingly recognized in the Pediatric population and poses significant clinical challenges. Timely and effective intervention is essential to prevent long-term complications such as recurrent infections, renal damage, or impaired growth. Percutaneous nephrolithotomy (PCNL) has emerged as a key surgical technique in managing moderate to large renal stones in children, but data on its efficacy and safety in the local context remain limited. Objectives: To assess the effectiveness of PCNL in achieving renal stone clearance in Pediatric patients aged 5 to 15 years presenting to a tertiary care centre in Khyber Pakhtunkhwa. Methods: This descriptive study was conducted at the Department of Urology, Institute of Kidney Diseases, Peshawar. A total of 216 children with uncomplicated, single renal stones measuring ≤8 mm, confirmed on a KUB X-ray, were enrolled through consecutive non-probability sampling. Standard PCNL was performed under general Anesthesia, and clearance was assessed postoperatively. Data were analyzed using SPSS version 23.0. Chi-square test was used for associations between stone clearance and variables age, gender, stone size, site, and operative time. Results: Stone clearance was achieved in 78.2% of cases. Clearance was higher in children with smaller stones (≤5 mm) and shorter operative times, though the differences were not significant (p>0.05). No major procedural complications were reported. Conclusions: PCNL is an effective and safe procedure for treating Pediatric renal stones. While factors like stone size and operative duration may influence outcomes, further large-scale studies are warranted to confirm these associations in the Pediatric population of low-resource settings.